Effects of common carp (Cyprinus carpio Linnaeus, 1758) supplementary feeding with modified cereals on pond water quality and nutrient budget. (30th June 2015) - Hlaváč, D.; Másílko, J.; Hartman, P.; Bláha, M.; Pechar, L.; Anton‐Pardo, M.; Adámek, Z.
Summary: This 4‐month study (10 May – 6 September 2012) evaluated the effects of supplementary feeding on common carp ( Cyprinus carpio Linnaeus, 1758) growth, water quality, natural food availability and nutrient balance under different pond treatment regimes (eight rectangular earthen ponds; 0.03 ha surface area; 3‐year‐old carp). The nitrogen and phosphorus budgets were calculated as the difference between input (food, fish stocked and influent water) and output (effluent water and fish harvested). Three types of supplementary feeds were used: wheat, thermally‐treated wheat, and thermally‐treated and pressed wheat. An additional test group was provided with naturally available forage only and served as a control. The type of supplementary feed did not influence the water quality, with the exception of dissolved oxygen. No significant differences among experimental ponds were observed in zooplankton abundance. The use of modified cereals (especially thermally‐treated and pressed wheat) improved carp growth performance and resulted in lower nutrient concentrations in effluent water via improving their digestibility. Both thermally‐treated and thermally‐treated and pressed cereals improved the balance of phosphorus; hence these diets could be beneficial, not only from the fish production point of view but also as a tool to reduce the deterioration of pond water quality.